Devitrification of ultrafast laser plasma produced metastable glass layer. (1st April 2017) - Chandrappan, Jayakrishnan; Khetan, Vishal; Ward, Michael; Murray, Matthew; Jose, Gin
Abstract: Erbium-doped tellurite modified silica (EDTS) is a newly formulated silicate glass that has the potential to realize on-chip optical amplifiers. The devitrification process of EDTS layer on host silica glass has been studied in the temperature range 300 °C–1000 °C. In-situ high-temperature X-ray diffraction, selective area electron diffraction and high-resolution transmission electron microscopy revealed the amorphous phase of EDTS as-fabricated up to 600 °C and rapid irreversible crystalline phase developments above 600 °C, contrasting the host silica. Distinct structural evolutions of EDTS with the variation in temperature were observed, including a complete evaporation of TeO2 at 800 °C from the matrix. Graphical abstract: